Operando investigations of lithiation and delithiation processes in a BiVO4 anode material. Issue 47 (22nd November 2018) - Ruud, Amund; Sottmann, Jonas; Vajeeston, Ponniah; Fjellvåg, Helmer
Abstract : Conversion and alloying reactions in BiVO4 as an anode material for lithium-ion batteries. Abstract : BiVO4 undergoes a series of conversion and alloying reactions as an anode material in lithium ion batteries. The current work demonstrates a charge capacity of 485 mA h g −1 after 50 cycles in a voltage range of 0–2.00 V (graphite has a capacity of 372 mA h g −1 theoretically). An exceptionally high volumetric capacity makes BiVO4 suitable for compact applications (volumetric capacity of 3984 mA h cm −3 for BiVO4 in comparison to 756 mA h cm −3 for graphite theoretically). Reaction steps and electronic transformations have been identified by operando quasi simultaneous synchrotron X-ray diffraction and absorption spectroscopy studies. An irreversible reaction step occurs for the Bi 3+ /Bi 0 redox pair, whereas reversible mechanisms are found for the V 5+ /V 3+ and Bi 0 /Bi 3− redox pairs. The proposed mechanisms are supported by density functional theory (DFT) calculations.